Konsep Pengelolaan Sampah Di Desa Babakan Kabupaten Bandung - Yonik Meilawati Yustiani; Anni Rochaeni; Elva Aulia (Universitas Lambung Mangkurat, 2019)
Residents and the government of Babakan Village have had difficulty managing their waste since the closure of the Babakan landfill several years ago. This study aims to formulate the concept of waste management in the Babakan Village, Bandung Regency, considering the waste generation and the characteristics of the residents. Data on the waste generation was obtained by sampling in several houses, while data on the characteristics of citizens was collected by distributing questionnaires. Based on the data gathered, it was found that the average waste generation per person per day in the Babakan Village was 0.134 kg with the composition of organic waste dominating up to 70.5%, while inorganic as much as 29.5%. The dominant types of waste in inorganic waste groups are plastic. In general, respondents have a good level of knowledge about waste. The enthusiasm of the community is high in participating to manage the waste with the 3R programs, such as recycling and operation of waste banks. With these data, the planning of handling of organic waste is done by a simple composter and biopori cylindrical water absorption hole, while handling inorganic waste can be done by operating a waste bank system.